Djamila Ribeiro e a agenda subjetivista - Rodrigues, Thiago William Santos (2022)
The theme of our research comprises the production of ideology in what refers to its origin and purpose. Thus, our work starts with the analysis of the historical development of ideology, where we intend to ascertain the emergence of subjectivism – arising from social and productive relations inherent in a class society –, and its manifestation in the work of Djamila Ribeiro. In any case, we will depart from the Marxist theoretical framework to understand the historical and concrete factors that allow the development of intellectual expressions, as well as revealing their roots linked to the interests and conceptions of a certain class. Thus, through bibliographical analysis, we consider Ribeiro production seeking to apprehend it from its connection with the totality of relations that constitute real life, observing his work as a product of determined social relations. Therefore, Ribeiro work is seen from the point of view of its correspondence with the interests of the ruling class, since it is subject to the bourgeois episteme and the set of ideologies that emerged during the late 20th century, having as a starting point the subjectivist paradigm.